KOLABORASI MULTIDISIPLIN: PEMBERDAYAAN IBU-IBU PKK BESERTA REMAJA DESA DALAM MENINGKATKAN KREATIVITAS DAN MELESTARIKAN BUDAYA LOKAL DESA MURBAYA, KABUPATEN LOMBOK TENGAH: Multidisciplinary Collaboration: Empowering Pkk Mothers And Village Youth In Improving Creativity And Preserving Local Culture In Murbaya Village, Central Lombok Regency - Pramastyo, Infanata Varel; Hasan, Rizqullah Al-Baiqi; Putriana, Amelia; Zakiani, Laila; Aprilani, Triana Lidona; Wijaya, Herman (Yayasan Al-Amin Qalbu, 2025)
The village of Murbaya located in Central Lombok has a very valuable local cultural heritage. However, this village is facing problems due to modernization and a lack of cultural regeneration among the youth. To address these issues, a community service program has been implemented with diverse approaches, involving the mothers of the PKK (Family Welfare Movement) and the youth as the main focus of empowerment. The goal of this program is to enhance the creativity of the community and preserve local culture through a combination of arts, education, and technology. Activities carried out include skill training both traditional and modern, arts and culture workshops, inter-generational dialogues, and the development of creative products based on local values. Cooperation among various age groups and different backgrounds successfully created effective communication channels, maximized the potential of the village, and strengthened collective awareness about the importance of promoting.